Behavior of Y-type perfobond rib shear connection under different cyclic loading conditions. (August 2020) - Kim, Kun-Soo; Han, Oneil; Heo, Won-Ho; Kim, Sang-Hyo
Highlights: We experimentally investigated behavior of Y-type perfobond rib shear connectors. Tests were conducted under fully reversed cyclic and pulsating loading conditions. Cyclic loading tests were conducted taking the number of cycles into consideration. Y-type shear connectors concentrate damage due to cyclic loads on concrete. Y-type perfobond rib shear connectors were not damaged even in extreme conditions. Abstract: A cyclic loading test is a simple method to determine the behavior of shear connection between steel and concrete. Tests using different cases of cyclic loading is necessary since most experimental programs considered limited loading conditions during reversed cyclic loading test. Various cyclic loading cases should be applied during cyclic tests in order to consider different situations. This study applied various cyclic loading cases to analyze and verify the effect of cyclic behavior on shear connection using stubby Y-type perfobond rib shear connectors. Our result show that the shear strength under cyclic loads was lower than that under monotonic load. Furthermore, plastic slip occurred after cyclic loads in each test.